Infection by Neopestalotiopsis spp. occurs on unwounded eucalyptus leaves and is favored by long periods of leaf wetness - Belisário, Renata (2018)
Brazil is the leader in the global ranking of forest productivity; however, one of the major challenges to eucalyptus production is the existence of fungal diseases. A severe epidemic caused by pestalotiopsis-like fungi was continuously observed in a forest nursery in Brazil, causing a huge impact on the eucalyptus micropropagation stages. The aims of the present study were (i) to identify the causal agent associated with pestalotiopsis leaf spot and dieback in eucalyptus; (ii) to assess the pathogenicity of the isolates to different commercial clones; (iii) to evaluate the wetness conditions that were favorable for both conidial germination and infection by the pathogen; (iv) to evaluate if pestalotioid fungi obtained from different host species could infect eucalyptus; and (v) to elucidate the fungal penetration process on eucalyptus leaves. Results showed that Neopestalotiopsis spp. are capable of causing symptoms on unwounded eucalyptus leaves and that disease development strongly requires specific environmental conditions. Therefore, our data demonstrate that long leaf wetness periods (≥ 72 h) were required to establish successful host–fungus relationships, causing expanded lesions to eucalyptus seedlings. Moreover, conidia germinated within 6 hours after inoculation and there was a tendency of direct germ tube penetration on host leaf tissues to reach a suitable infection. All of the four commercial clones tested were susceptible to the pathogen and the set of data disputes the assumption that pestalotioid fungi are weak and opportunistic. Our data imply that single- gene phylogenetic trees constructed from ITS and TEF regions showed unresolved polytomies (multifurcating branches) and poor resolution. Only TUB and multi-locus phylogenies were stable and provided sufficient resolution tree topologies. This is the first report of different phylogenetic species of Neopestalotiopsis causing dieback, leaf and stem lesions in eucalyptus seedlings. Considering the importance of this pathogen on aerial parts of eucalyptus, comprehension of the favorable conditions required for disease progress may provide a basis for developing novel management strategies in forest nurseries.